Tight glycemic control in the ICU - is the earth flat? - Steil, Garry M (BioMed Central, 2014)
Tight glycemic control in the ICU has been shown to reduce mortality in some but not all prospective randomized control trials. Confounding the interpretation of these studies are differences in how the control was achieved and underlying incidence of hypoglycemia, which can be expected to be affected by the introduction of continuous glucose monitoring (CGM). In this issue of Critical Care, a consensus panel provides a list of the research priorities they believe are needed for CGM to become routine practice in the ICU. We reflect on these recommendations and consider the implications for using CGM today.